Keberterimaan Amil Zakat LAZIS NU dan LAZIS Muhammadiyah terhadap Hegemoni Negara dalam Pengelolaan Zakat - Muhamad Nasrudin (Postgraduate State Islamic Institute (IAIN) Metro, 2017)
While many Zakat Management Organizations (ZMO) rejected state hegemony through Law No. 23/2011 on Zakat Management, LAZIS NU and LAZIS Muhammadiyah, two ZMO from the largest Islamic organizations in Indonesia have little to say, even tend to be silent. From here, this paper seeks to find out and reconstruct acceptence of two LAZISs to the state hegemony in the management of zakat. Both LAZISs have acceptance that tend to be neutral and even lead to positive. This is because, Law No 23/2011 is considered in harmony with the function and role of the State and it supports civil society. Implicitly, both organizations affirm UUPZ 23/2011 because it is not affected by the hegemonic state.